The Use Of Wordlist To Enrich Students’ Vocabulary Memorization At Sma Negeri 2 Tondano - Paudi, Stalsa; Hampp, Paula; Maukar, Merlin (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
The aim of this research was to see whether the use of a wordlist can improve students’ vocabulary memorization or not. This research was conducted at the eleventh grade of SMA NEGERI 2 Tondano, class XI was chosen as the subject of the study and this class consists of twelve (12) students. This research used a pre-experimental design with one group pre-test and post-test. The instrument for data collection is an objective test. This research showed that the mean score of the pre-test is 68% for basic vocabulary numbering 30 and 20% for vocabulary in the book and the post-test is 85%. This means that the result of the post-test is higher than the pre-test. In other words, this result may lead to the conclusion that using the use of wordlist is effective in improving students’ vocabulary in the 12th grade of SMA Negeri 2 Tondano. This shows that English Teachers can use a wordlist to enrich and improve students’ vocabulary memorization